(3HOGFY GdWdHGJ hefJgi GdZGjGJs
(3ChdgG (B:s
(3GdedJeS gh EJMGO GdYfGUQ MJi dGjJejR EMOgeG Yf GdGNQ WHYkG hdG MSG hgh CUYH eG JYGWhg ai GdJOGHjQ s
(3BNQgG (B:s
(3abO ESJeJYJ HgG hbO LYdJ gPg GdMcGjI YTQI GHhGH dJchf def hUdJ Edjg HYOi YhfkG Ydi eWdhHg hSHHkG ddOYGA dfG Ydi ELJgGOfG hbO SejJ cd cJGH efgG HGSe aSejJ LedI GdcJGH HOGjY GdWdHGJ hefgi GdZGjGJ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs